Efficacy and safety of parathyroid perfusion assessment by fine-needle prick during thyroid surgery: a prospective study - Wang, Peisong; Xue, Haowen; Wang, Xin; Xue, Shuai (Frontiers in Endocrinology, 2025)
ObjectiveThis prospective study aimed to analyze the efficacy and safety of fine-needle prick (FNP) in the assessment of parathyroid gland (PG) perfusion during thyroid surgery.MethodsA total of 147 patients with papillary thyroid carcinoma (PTC) who underwent lobectomy with therapeutic unilateral central lymph node dissection (CLND) performed by the same surgeon at the First Hospital of Jilin University between June and September 2024 were included in this prospective study. Following removal of the thyroid and unilateral central lymph nodes, indocyanine green (ICG) was prepared and administered intravenously. Fluorescence signals and images were captured using a near-infrared system to obtain the ICG1 score. Approximately 5–10 min thereafter, the fluorescent signal dissipated, after which the preserved PG was evaluated using FNP. An FNP score was established based on oozing blood from the parathyroid. After hemostasis was achieved by compression with gauze, ICG was reinjected to reassess PG perfusion, which yields the ICG2 score.ResultsIn 13 patients, only one parathyroid was identified, while the other was inadvertently excised during surgery. A total of 269 (95.73%) parathyroids were evaluated, with consistent scores observed between the use of the ICG1 and FNP methods. However, in six congested PGs with a darkened appearance, the FNP method could not accurately assess blood supply due to the slow oozing of accumulated blood following the procedure. The Spearman’s correlation coefficient between the ICG1 and FNP methods was 0.973 (p < 0.001), demonstrating strong concordance in determining PG blood supply. Furthermore, the identical ICG1 and ICG2 scores indicated that FNP did not adversely affect PG perfusion.ConclusionThe FNP test could represent a safer, simpler, and more reliable alternative to ICG for the assessment of PG perfusion. However, further validation in patients undergoing total thyroidectomy and bilateral CLND is warranted.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2400084531.